2007
DOI: 10.1017/s1751731107000602
|View full text |Cite
|
Sign up to set email alerts
|

Responses to nutrients in farm animals: implications for production and quality

Abstract: It is well known that any quantitative (energy and protein levels) and qualitative (nature of the diet, nutrient dynamic) changes in the feeding of animals affect metabolism. Energy expenditure and feed efficiency at the whole-body level, nutrient partitioning between and within tissues and organs and, ultimately, tissue and organ characteristics are the major regulated traits with consequences on the quality of the meat and milk produced. Recent progress in biology has brought to light important biological me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 126 publications
0
25
0
1
Order By: Relevance
“…Grazing, as compared to indoor fattening, results in a different fatty acid composition (higher proportions of linoleic and linolenic acid), darker and redder meat with better sensory qualities and an increased shelflife (Dieguez et al 2006;Farruggia et al 2008;Fraser et al 2009;Hocquette et al 2007). Fraser et al (2009) conducted grazing experiments with different breeds on improved permanent pasture (ryegrass/clover) and semi-natural rough grazing on Molinia caerulea dominated swards.…”
Section: Diversity and Other Services For Livestock Productionmentioning
confidence: 99%
“…Grazing, as compared to indoor fattening, results in a different fatty acid composition (higher proportions of linoleic and linolenic acid), darker and redder meat with better sensory qualities and an increased shelflife (Dieguez et al 2006;Farruggia et al 2008;Fraser et al 2009;Hocquette et al 2007). Fraser et al (2009) conducted grazing experiments with different breeds on improved permanent pasture (ryegrass/clover) and semi-natural rough grazing on Molinia caerulea dominated swards.…”
Section: Diversity and Other Services For Livestock Productionmentioning
confidence: 99%
“…However, this competitive interaction between nutrients might not be as marked in the case of increased energy requirements resulting from higher rates of protein synthesis and deposition. Conversely, stimulation of carbohydrate catabolism, for instance by insulin, may inhibit long-chain fatty acid oxidation (reviewed by Hocquette et al, 2007c). We observed that a high supply of sunflower oil or linseed oil directly infused into the proximal duodenum modified the metabolic activity of muscles.…”
Section: Regulation Of Metabolism By Nutrition In Veal Calvesmentioning
confidence: 81%
“…Over the last few decades, a vast amount of research has been conducted to understand the metabolic and hormonal regulation of muscle growth and body composition (Etherton, 2009). This review aims to summarise the progress in knowledge in this specific area with a focus on the recent contribution of genomics 2009) to decipher these biological processes and as a complement to a previous review describing the responses to nutrients in farm animals in all organs and tissues (Hocquette et al, 2007c). This paper is divided into two sections that deal with the metabolic and hormonal regulation of muscle growth before birth and after parturition, which are two different periods in terms of muscle growth.…”
Section: Introductionmentioning
confidence: 99%
“…Two examples of potential confounding factors associated with a high NFC diet are the energy content of the diet and the effect of NFC on glucose and insulin. The increase in dietary energy resulting from higher NFC could ultimately be a confounding factor of the NFC diet because of carbohydrate stimulation on ATP production in muscle tissue (Hocquette et al 2007), perhaps affecting muscle proteolysis. Use of high grain diets is also known to stimulate insulin response and increase Fig.…”
Section: Resultsmentioning
confidence: 99%